Identification and validation of SNHG gene signature to predict malignant behaviors and therapeutic responses in glioblastoma - Fan, Yang; Gao, Zijie; Xu, Jianye; Wang, Huizhi; Guo, Qindong; Xue, Hao; Zhao, Rongrong; Guo, Xing; Li, Gang (Frontiers in Immunology, 2022)
Glioblastoma (GBM) patients exhibit high mortality and recurrence rates despite multimodal therapy. Small nucleolar RNA host genes (SNHGs) are a group of long noncoding RNAs that perform a wide range of biological functions. We aimed to reveal the role of SNHGs in GBM subtypes, cell infiltration into the tumor microenvironment (TME), and stemness characteristics. SNHG interaction patterns were determined based on 25 SNHGs and systematically correlated with GBM subtypes, TME and stemness characteristics. The SNHG interaction score (SNHGscore) model was generated to quantify SNHG interaction patterns. The high SNHGscore group was characterized by a poor prognosis, the mesenchymal (MES) subtype, the infiltration of suppressive immune cells and a differentiated phenotype. Further analysis indicated that high SNHGscore was associated with a weaker response to anti-PD-1/L1 immunotherapy. Tumor cells with high SNHG scores were more sensitive to drugs targeting the EGFR and ERK-MAPK signaling pathways. Finally, we assessed SNHG interaction patterns in multiple cancers to verify their universality. This is a novel and comprehensive study that provides targeted therapeutic strategies based on SNHG interactions. Our work highlights the crosstalk and potential clinical utility of SNHG interactions in cancer therapy.